2008
DOI: 10.1016/j.jvs.2008.01.048
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metabolic syndrome components on exercise performance in patients with intermittent claudication

Abstract: PAD patients with more metabolic syndrome components have worsened intermittent claudication, physical function, health-related quality of life, and peripheral circulation. Abdominal obesity and elevated fasting glucose are the metabolic syndrome components that are most predictive of these outcome measures. Aggressively treating these metabolic syndrome components may be particularly important in managing symptoms and long-term prognosis of PAD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 35 publications
6
49
0
2
Order By: Relevance
“…Whether these metabolic abnormalities contribute to exercise limitation in symptomatic PAD patients has not been studied, but recent evidence that claudicants with metabolic syndrome have reduced maximal and pain-free walking times compared with PAD subjects without features of the metabolic syndrome supports this hypothesis. 14,24 However, given the crosssectional nature of our findings and the data in the existing literature, we do not know whether insulin resistance is a contributor to claudication symptoms or arises secondarily as a result of reduced physical activity. [25][26][27] Future studies will be necessary to explore whether improving insulin sensitivity can increase functional capacity in patients with PAD.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Whether these metabolic abnormalities contribute to exercise limitation in symptomatic PAD patients has not been studied, but recent evidence that claudicants with metabolic syndrome have reduced maximal and pain-free walking times compared with PAD subjects without features of the metabolic syndrome supports this hypothesis. 14,24 However, given the crosssectional nature of our findings and the data in the existing literature, we do not know whether insulin resistance is a contributor to claudication symptoms or arises secondarily as a result of reduced physical activity. [25][26][27] Future studies will be necessary to explore whether improving insulin sensitivity can increase functional capacity in patients with PAD.…”
Section: Discussionmentioning
confidence: 72%
“…12,13 Furthermore, Gardner and Montgomery have shown that PAD patients with features of the metabolic syndrome have reduced walking times. 14 Direct quantification of insulin-mediated glucose uptake in skeletal muscle can be achieved with dynamic positron emission tomography (PET) imaging with the radioisotope [ 18 F]fluorodeoxyglucose (FDG). Prior studies in subjects with diabetes and coronary artery disease have demonstrated decreased skeletal muscle FDG uptake, as would occur with insulin resistance, in the myocardium and skeletal muscles of the upper extremities, 15,16 but no prior studies have evaluated glucose uptake in subjects with PAD.…”
mentioning
confidence: 99%
“…14,[25][26][27] Other studies, however, have shown that ABI is not strongly associated with exercise performance in symptomatic PAD patients. [6][7][8][9][28][29][30] In 133 patients with intermittent claudication, walking distance was lower in groups of patients with a progressively higher number of metabolic syndrome components, despite similar mean ABI across all groups. 30 In 66 patients with claudication, neither resting ABI (r = 0.14, p = NS) nor post-exercise ABI (r = 0.11, p = NS) correlated with absolute claudication time, and ABI was not significantly different between patients with short and long claudication distances.…”
Section: Factors Influencing Functional Performance In Patients With Padmentioning
confidence: 98%
“…With specific attention to the skeletal muscle circulation and its role in the development of PVD, there has been an enormous accumulation of knowledge regarding associations between elevated PVD risk, specific structural or functional markers of vascular dysfunction, putative mechanistic contributors and indexes of perfusion-based deficits, and impaired tissue/organ function (11,25,26,38,46). While this previous work has shed considerable light on what is a very complicated issue, it has proven very difficult to assign and understand the multiscale nature of PVD risk and negative vascular outcomes both within and across models of pathology.…”
Section: Linking Peripheral Vascular Disease (Pvd) Risk To Integratedmentioning
confidence: 99%